THE USE OF COMBINED TREATMENT OF MICROBIAL ECZEMA WITH THE PREPARATION BETAMETHASONE-DARNITSA (ResearchJet Journal of Analysis and Inventions, 2021)
In our work, we observed patients with microbial eczema who received the cream "betamethasone-darnitsa" against the background of standard treatment.15 patients aged 18 to 42 years were examined. Women – 5, men-13. On average, the duration of the disease ranged from 2 months to 5 years. Based on our research, we made the following conclusions: the drug "Betamethasone-Darnitsa" has a high therapeutic effectiveness and can be used in the treatment of patients with microbial eczema.